Analysis of coupled and decoupled PWM techniques for induction motor drive - Syed Munvar Ali; V Vijaya Kumar Reddy; M Surya Kalavathi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Dual inverter fed induction motor drive-in open-end winding gives more advantages than multilevel inverter fed induction motor drives. For better quality of output voltage with low common mode voltage (CMV), in this paper analysis of coupled and decoupled PWM techniques for open end winding induction motor are carried. The analysis is carried in MATLAB/simulink environment for vector controlled open end winding induction motor drive. The performance of drive and PWM techniques are evaluated both in transient, steady state and loaded conditions.